Analyzing Code Switching Used as a Bridge of Misunderstanding in Classroom for Students at SMAN 1 Deli Tua - Dicky Rozaki; Rahmawati Rahmawati; Ernita Daulay (Randwick International of Education and Linguistics Science Journal, 2023)
This research was directed to analyze (1) the types of code switching used in classroom during the English course (2) the reasons why teachers and students at SMA Negeri 1 DELI TUA using code switching in class and (3) the effect of code switching. The researcher adopted descriptive- qualitative method since the data dealt with words instead of numbers and applied Hoffman theory to analyze the problems. Technique for collecting data used by researcher was triangulations, those are observation, questionnaires, and interview. Intra sentential switching, Establishing continuity with previous speaker , and Emblematic got 22,22%, and each Inter sentential switching, Intra lexical and Involving a Change of Pronunciation are 11,11% percentages. There are several code switching occurred on the class and researcher placed based on the functions and they are 57,14% of Repetitive function, 28,57% of Interjection and the last is 14,28% for Quoting somebody else is found during the observation.